Diversity Of Weed Species In Cocoa Plantations In Banyuwangi, East Java, Indonesia - Syaiful Khoiri; Shafira Desty Adisa; Dheananda Fyora Hermansyah Azari; Dita Megasari (Jurnal Riset Perkebunan, 2023)
Cocoa (Theobroma cacao L.) is one of the important plantation commodities in Indonesia. However, one of the factors that can affect productivity is weeds because weeds compete with cocoa in getting water, sunlight, nutrients, air, and space to grow. One of the largest cocoa plantation areas in East Java is the Banyuwangi district. Information about the types of cocoa weeds in Banyuwangi is unknown even though weeds in one area are different from another. Weed can reduce the production of cocoa. So, This study is important for determining appropriate control methods. This study aimed to determine the type, diversity, and abundance of weeds. The research method used in this study was a survey with a square-plot size. All weed samples were identified. The results showed that there were twelve types of broadleaf weeds, three types of grass weeds, one type of sedge, and one type of fern. The highest importance value index (IVI) was found in Ottochloa nodosa at 40.91%. The diversity of weeds was in a medium category. Weed diversity in cocoa plantations in Banyuwangi was different from other areas in Indonesia. The results of this research contribute to providing information on the diversity of weeds that can be used in determining weed control strategies in cocoa plantations.